The Elusive Norm of Climate Responsibility:The Belt and Road Initiative and COVID-19 - Kopra, Sanna; Nojonen, Matti (2020)
Based on the premise that climate responsibility had emerged as an international norm in the pre-coronavirus era, this paper studies to what extent the coronavirus is challenging the policies and strategies of China’s Belt and Road Initiative (BRI) and its offspring the Polar Silk Road. We begin with a critical overview of the BRI and illustrate the practical implications of the fact that the BRI lacks an official strategy, a definition and a governing institution. We elaborate what kind of discourses and standards are attached to the BRI in general, and its latest addition, the Polar Silk Road, in particular. On the one hand, we analyze how China’s pre-COVID-19 era Arctic policy and BRI documents (and norms) manifested and set the standards of climate responsibility, and, on the other hand, based on original Chinese policy documents, we debunk how these lofty political goals were rapidly and completely set aside as the new coronavirus epidemic was spreading around. Instead, the Party hastily made stipulations and policies and refocused the BRI to save Chinese overseas investments and the reputation of China in the post-coronavirus era.